2018
DOI: 10.1177/0022042618795141
|View full text |Cite
|
Sign up to set email alerts
|

Risky Sexual Behaviors, Substance Use, and Perceptions of Risky Behaviors Among Criminal Justice Involved Women Who Trade Sex

Abstract: This study examined risky sexual behaviors, Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV)-defined alcohol and substance use disorders, and perceptions of risky behaviors among community released, justice-involved women, who are currently trading sex (CTS), formerly traded sex (FTS), or have never traded sex. Data were derived from 266 sexually active women recruited from a Municipal Drug Court System in St. Louis, Missouri. In an adjusted multinomial regression model, being dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…[ 22 23 ] Jones et al . [ 10 ] showed that there was a significant relationship between a low level of education and involvement in exchange sex (the exchange of monetary or non-monetary items for sex). Marital status: Only two studies have surveyed the relationship between marital status and the involvement of women drug users in risky sexual behaviors whose findings are somewhat contradictory.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 22 23 ] Jones et al . [ 10 ] showed that there was a significant relationship between a low level of education and involvement in exchange sex (the exchange of monetary or non-monetary items for sex). Marital status: Only two studies have surveyed the relationship between marital status and the involvement of women drug users in risky sexual behaviors whose findings are somewhat contradictory.…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 23 ] Jones et al . [ 10 ] showed that there was a significant relationship between a low level of education and involvement in exchange sex (the exchange of monetary or non-monetary items for sex).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations